On the performance study of a hybrid indirect evaporative cooling and latent-heat thermal energy storage system under commercial operating conditions. (25th February 2023) - Wan, Yangda; Huang, Zhifeng; Soh, Alexander; Jon Chua, Kian
Highlights: A hybrid IEC-LHTES cooling system is proposed under commercial conditions. Experimental system comprising the IEC with the LHTES is designed and tested. Mathematical models are judiciously developed to simulate transport phenomena. Effects of the climatic and operating conditions are investigated in detail. Abstract: In this paper, a hybrid evaporatively-enhanced cooling system is proposed under commercial operating conditions. The indirect evaporative cooler (IEC) is first employed as a pre-cooling equipment to treat ambient air by recovering energy from the indoor exhaust air. The pre-cooled air is then treated to achieve the required thermal condition by employing the latent-heat thermal energy storage (LHTES) containing spherical balls encapsulated with a synthesized phase change material (PCM). Such a novel hybrid process takes full advantage of the IEC's high cooling efficiency and LHTES's power peak load shifting capability. Experimental system comprising the IEC integrated with the LHTES is designed and tested under various air conditions. Additionally, mathematical models are developed to simulate transport phenomena behind the system. Employing experimentally-validated models, thermodynamic analyses are conducted to study the system's performance. Results indicate that (1) the proposed hybrid system is able to pre-cool and dehumidify the ambient air in the tropics simultaneously; (2) the ambient air temperature and humidity ratio can be respectively reduced by 6–10 °C and 2–11 g/kg dry air under specific operating ranges; (3) the evaporative cooling technology facilitates the use of a higher chilled water supply temperature which results in an improvement on the chiller efficiency; and (4) a higher water flow rate leads to faster cold energy storage and release rates during the respective charging and discharging periods.